Research of Foam Gypsum Drying Process and Heat Flow Transfer - R. Brencis; U. Iljins; J. Skujans; U. Gross (Chemical Engineering Transactions, 2012)
Nowadays the house building technical progress is aimed to use materials with preferable properties. Foam gypsum on gypsum basis is one of these materials, and drying of foam gypsum is an obligatory condition of technological process. This drying process and its energy consumption have been researched theoretically and experimentally in this paper. The characteristic parameters of foam gypsum drying process depending on volume density of material have been determined. Heat flow transfer in foam gypsum drying process has been researched experimentally. Mathematical model of heat flow transfer of drying process has been developed. The thickness of layer for effective drying has been determined.